Motivational Pathways to Success in English Language Learning: Insights from Higher Education - Widiarsih, Ivana Carla Monica; Kuswandono, Paulus (Jurnal Studi Guru dan Pembelajaran, 2024)
Knowing the driving factors in achieving something is necessary. whether based on the outside or from oneself. The objective of this study is to establish the levels of self-determination of English language students with attention, relevance, confidence, and satisfaction (ARCS Model). The achievement of understanding English depends on the degree of motivation demonstrated by the student, which may be classified as intrinsic or extrinsic. The research population comprised a few students from each class enrolled in an English Educational Program during the odd semesters of the academic year 2023/2024 at Satya Wiyata Mandala University. The Data is gathered from 40 students in total via questionnaires and interviews within a mixed-method research technique adopted in the study. Data was gathered via questionnaires and interviews. The questionnaire was developed using Gardner’s Attitude Motivation Test Battery (AMTB). The study employed a Likert Scale instrument with the 5-point rating system for quantitative data, which was developed based on the Likert Scale Format. The replacement was supplied by students in the questionnaire and interviews were used to generate the study’s conclusions. The participants exhibited higher levels of intrinsic motivation (M = 3.9) compared to extrinsic motivation (M = 3.7).